2022
DOI: 10.3389/fimmu.2022.1018423
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic insights into the immune response and pearl formation in transplanted pearl oyster Pinctada fucata martensii

Abstract: During pearl culture, the excess immune responses may induce nucleus rejection and death of pearl oysters after transplantation. To better understand the immune response and pearl formation, lipidomic analysis was applied to investigate changes in the serum lipid profile of pearl oyster Pinctada fucata martensii following transplantation. In total, 296 lipid species were identified by absolute quantitation. During wound healing, the content of TG and DG initially increased and then decreased after 3 days of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…We also found that ABC transporters, arachidonic acid metabolism, linoleic acid metabolism, antifolate resistance and ovarian steroidogenesis gene families contracted significantly in the snails, which may be related to feeding habits, reproductive, environmental adaptation and immune defense behavior [ 49 51 ]. In China, the ribbed-shell snail populations and the smooth-shell snail populations are distributed in different ecological environments, and their compatibility with S. japonicum is also different.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that ABC transporters, arachidonic acid metabolism, linoleic acid metabolism, antifolate resistance and ovarian steroidogenesis gene families contracted significantly in the snails, which may be related to feeding habits, reproductive, environmental adaptation and immune defense behavior [ 49 51 ]. In China, the ribbed-shell snail populations and the smooth-shell snail populations are distributed in different ecological environments, and their compatibility with S. japonicum is also different.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that ABC transporters, arachidonic acid metabolism, linoleic acid metabolism, antifolate resistance and ovarian steroidogenesis gene families contracted signi cantly in the snails, which may be related to feeding habits, reproductive, environmental adaptation and immune defense behavior [45][46][47].…”
Section: Discussionmentioning
confidence: 99%